The Impact of Regular Exercise, Competition Experience, and Physical Self-efficacy on Psychological Resilience - Dong Hwan Kim; Jeong Hu Kim; Kyong-Jun Park (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The concept of resilience has a crucial role in various aspects of individuals' lives, including physical exercise, self-efficacy, self-esteem, body image, and overall welfare. The importance of this factor in assisting athletes in effectively navigating the demands of sports performance should not be underestimated. The present study aims to investigate the effects of consistent physical exercise and participation in competitive activities on an individual's psychological resilience. A cross-sectional analysis was conducted on a sample of 329 participants, consisting of 229 individuals who engaged in regular exercise and 100 individuals who did not exercise. The participants were selected from athletics club members and college students. The Resilience Scale and Physical Self-Efficacy Questionnaire were administered to the participants using a survey conducted through Google Forms. Prior informed consent was obtained from all participants. The findings suggest that those in the regular exercise group had enhanced emotional impulse control, heightened positive emotions, improved communication skills, more empathy, and greater self-improvement in comparison to those in the non-exercise group. In a similar vein, individuals who took part in competitive activities had a significant improvement in their ability to regulate their emotional impulses, showed a greater understanding and management of positive emotions, exhibited improved communication abilities, displayed heightened empathetic capacities, and experienced enhanced personal growth compared to those who did not participate. The aforementioned results highlight the beneficial impact of consistent physical activity in strengthening one's psychological resilience, which is consistent with previous research that has demonstrated exercise's ability to reduce stress and enhance resilience. This study highlights the positive associations between consistent physical activity, engagement in competitive sports, and increased psychological resilience among athletes. Examining these connections offers practical knowledge for athletes and sports professionals aiming to enhance their psychological well-being and performance in demanding environments.